2013
DOI: 10.1371/journal.pone.0054454
|View full text |Cite
|
Sign up to set email alerts
|

Sod1 Deficiency Reduces Incubation Time in Mouse Models of Prion Disease

Abstract: Prion infections, causing neurodegenerative conditions such as Creutzfeldt-Jakob disease and kuru in humans, scrapie in sheep and BSE in cattle are characterised by prolonged and variable incubation periods that are faithfully reproduced in mouse models. Incubation time is partly determined by genetic factors including polymorphisms in the prion protein gene. Quantitative trait loci studies in mice and human genome-wide association studies have confirmed that multiple genes are involved. Candidate gene approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 45 publications
0
18
0
1
Order By: Relevance
“…This protection was revealed to be due to alterations study showed a correlation between SNPs in the Il1r1 locus and incubation time in mouse models of prion diseases, supporting the involvement of IL-1R1 signaling in prion pathogenesis (66). Several antiinflammatory cytokines have been examined for their contribution to prion disease.…”
Section: Microglia-related Transducers In Prion Diseasesmentioning
confidence: 81%
“…This protection was revealed to be due to alterations study showed a correlation between SNPs in the Il1r1 locus and incubation time in mouse models of prion diseases, supporting the involvement of IL-1R1 signaling in prion pathogenesis (66). Several antiinflammatory cytokines have been examined for their contribution to prion disease.…”
Section: Microglia-related Transducers In Prion Diseasesmentioning
confidence: 81%
“…SOD2 downregulation has previously been associated with prion infection in vivo (Choi et al, 1998; Lee et al, 1999; Park et al, 2011). Although these studies did not report an increase in SOD1 activity, regulation of SOD1 activity by PrP has also been reported (Brown et al, 1997; Sakudo et al, 2005) and SOD1 knockout has been shown to significantly reduce disease incubation time in murine models of prion disease (Akhtar et al, 2013). In the current system, the increased SOD1 activity might explain how the majority of moRK13 cells are able to remain viable in culture, despite reduced SOD2 levels, while propagating infection over long periods of time.…”
Section: Discussionmentioning
confidence: 96%
“…These included PRNP, RARB-THRB, STMN2, HECTD2, SPRN, ZBTB38-RASA, BACE, MTMR7, NPAS2, PLCD, CPNE8, SOD1, STCH and CTSD [2,3,19,21,22,29,30,36]. No CNV overlapping these genes was found in more than one individual in a case or control group (table 1 supplementary).…”
Section: Cnvs Overlapping Loci Of Potential Relevance To Prion Diseasementioning
confidence: 96%
“…Several large-scale association studies have reported a role for large CNVs in susceptibility to several human conditions including idiopathic epilepsy, attention deficit hyperactivity disorder, schizophrenia, bipolar disorder, mental retardation, autism, and Alzheimer's disease [1,6,13,14,25,26,40] [2,3,19,21,22,29,30,36]. As a generalisation, few common structural genetic variations are risk factors in common diseases [10], whereas several rare CNVs, including whole or partial gene deletions and/or duplications are known to be major risk factors and/or dominantly inherited disease causing mutations in neurodegenerative diseases [1,13,14,25,26,35,40].…”
Section: Introductionmentioning
confidence: 99%